Effects of orexin receptor antagonism on human sleep architecture: A systematic review. (October 2020) - Clark, Jacob W.; Brian, Maddison L.; Drummond, Sean P.A.; Hoyer, Daniel; Jacobson, Laura H.
Summary: Orexin receptor antagonists are a relatively new hypnotic principle. Their influence on human sleep architecture is a point of debate that has not been systematically evaluated. Thus, we performed a systematic review to assess how these compounds effect sleep architecture in healthy and clinical human samples. Relevant articles were identified via searches of PubMed, Embase, the Cochrane central register of controlled trials, and clinicaltrials. gov. From 1147 retrieved records, 18 satisfied inclusion criteria and formed the basis of this review. Of these, fifteen studies administered dual orexin receptor antagonists (DORA) in a healthy control (five studies) or clinical sample (ten studies). By contrast, three studies administered selective orexin receptor-2 antagonists (2-SORA) in either a healthy control (one study) or clinical sample (two studies). Results reveal DORAs increase total sleep time primarily by promoting REM sleep, without affecting, or even decreasing, non-REM sleep, especially in clinical samples. Therefore, the clinical utility of DORAs may depend on the specific sample being treated. For 2-SORAs, limited evidence available precludes firm conclusions about their influence on human sleep architecture and, thus, further investigation of 2-SORAs is required to define their effects and make comparisons on this basis with DORAs.